2019
DOI: 10.3390/rs11232732
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Observation of Thunderstorm-Induced Ionospheric Gravity Waves above Low-Latitude Areas in the Northern Hemisphere

Abstract: Gravity waves (GWs) generated in the lower atmosphere can propagate upwards to ionospheric height. In this study, we investigated the correlation between ionospheric GWs detected by Global Navigation Satellite System (GNSS)-derived total electron content data and thunderstorm events recorded by a local lightning-detection network in the low-latitude region of Southern China during a four-year period, from 2014 to 2017. Ionospheric GWs were detected on both thunderstorm and non-thunderstorm days. Daytime ionosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…the HK SatRef are quite close; hence, similar observations are made by most stations at a given time [14]. Only observations from station HKOH meeting the criteria in Section 2.4 are presented.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…the HK SatRef are quite close; hence, similar observations are made by most stations at a given time [14]. Only observations from station HKOH meeting the criteria in Section 2.4 are presented.…”
Section: Resultsmentioning
confidence: 60%
“…Mahmud M [13], who also studied thunderstorm events over Southern Africa, showed that a strong correlation exists between hourly lightning and ionosphere irregularity event occurrence. Recent studies by Tang, et al [14] and Liu, et al [15] showed the characteristics of thunderstorm generated ionosphere gravity waves (IGW) in the Southern China region.…”
Section: Introductionmentioning
confidence: 99%
“…However, our work is based on direct measurement of TEC above thunderstorm events and their responses, with more focus on the gravity wave effects. Although a recent contribution by Tang et al (2019) focused on the contribution of gravity wave, however, their work only covers the low latitude region from ~14°N to 25°N close to Hong Kong and its surroundings, which is far greater 1500 km from low latitude/equatorial region 17 . It is therefore pertinent to consider investigations around the low/latitude equatorial region, considering the fact that the ionospheric processes, dynamics and responses to external influence vary with proximity to the equator.…”
mentioning
confidence: 99%
“…As seen in Figure 9, thunderstorm activity during the summer solstice was significantly stronger than during the winter solstice. Tang et al [29] analyzed the relationship between thunderstorms and the ionospheric GWs over the Hong Kong area during the years of 2014-2017. Their research indicated that thunderstorm events were the main source of GWs, especially during high thunderstorm days, such as the summer solstice.…”
Section: Discussionmentioning
confidence: 99%
“…According to the local VLF detection network, the Hong Kong area had frequent thunderstorm activity during March-October. Using the processing method in Tang et al [29], we obtained the average thunderstorm coverage area (grid counts) for different seasons during each year from 2014 to 2017, shown in Figure 9. As seen in Figure 9, thunderstorm activity during the summer solstice was significantly stronger than during the winter solstice.…”
Section: Discussionmentioning
confidence: 99%